Differential brain expression of 3R and 4R Tau isoforms in aging wild‐type and young genetically engineered PSEN1 mutant marmosets. (20th December 2022) - Rizzo, Stacey J Sukoff; Choi, Sang‐Ho; Huhe, Hasi; Kofler, Julia; Schaeffer, David; Murai, Takeshi; Hachem, Stephanie; Karavolis, Marlena; Mou, Yongshan; Ha, Seung‐Kwon; Carter, Gregory W; Park, Jung Eun; et al.
Abstract: Background: The common marmoset ( Callithrix jacchus ) has emerged as an important model for studying Alzheimer's disease (AD). Several previous publications reported the natural and spontaneous accumulation of Aβ aggregates in aging marmosets. However, the presentation of tau in aging marmosets has been understudied. A recent report investigated the expression of different tau isoforms and concluded that only 4R tau is expressed throughout adulthood (Sharma et al., J. Biol. Chem. 2019). Here, we investigated the presence of amyloid and tau aggregates in aged wild‐type marmosets and in young adult individuals genetically engineered with knock‐in (KI) point mutations in the PSEN1 gene that cause early‐onset AD. Method: We used standard IHC protocols and western blotting techniques with validated antibodies for amyloid (NAB228) and tau (RD3, 3T3, PHF‐1) to investigate the presence and localization of AD aggregates in the brains of 5 marmosets (n = 3 wild‐type and 2 PSEN1 KI mutants). Result: We observed the natural accumulation of amyloid aggregates with the anti‐amyloid antibody NAB228 in a 10‐year male marmoset that confirms this subject's previous in vivo evaluation with 11 C‐PiB PET imaging. Interestingly, this aged marmoset showed positive 3R and 4R tau staining with the anti‐tau antibodies RD3 and 3T3, respectively (Figure 1 ) in the hippocampus. In agreement with Sharma et al., 2019, tau staining in the hippocampus was much more abundant for the 4R than the 3R tau isoform, with substantial phosphorylation at Ser‐396 and Ser‐404. We detected no tau staining in the entorhinal cortex of this animal and no amyloid nor tau in the brain of a one‐year‐old juvenile. We observed similar results of significant amyloid accumulation and RD3 and 3T3 labeling in the brains of two young (18 months) PSEN1 KI mutants. Separately, we confirmed by western blot 3R and 4R tau isoforms in homogenates from the hippocampus and entorhinal cortex of three individual marmosets (aged 1‐7 years). Conclusion: Our genetically diverse marmoset population of aging and PSEN1 mutation carriers present both 3R and 4R isoforms across the lifespan. These data further support marmosets as an ideal species for translational studies of AD. Studies in larger sample sizes are ongoing.